2010
DOI: 10.1111/j.1745-4514.2010.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Steeping: A Way of Improving the Malting of Rice Grain

Abstract: Water availability significantly affects the mechanism through which grain is converted into malt. High moisture content enhances enzyme production and shoot emergence. To examine this effect on rice malt, rice grains were soaked for different periods with the aim of establishing the optimum that significantly affects the final malt quality. The out-of-steep moisture content (SMC), steeping loss, germination energy, shoot length and the diastatic activity of the malt were evaluated.Statistical Analysis indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The longer steeping duration resulting in reduced sprout length was reported by [79]. The shortest sprout length was observed in Thai rice malt cultivars (Oryza sativa L. Indica) steeped for 72 h, followed by 48 and 24 h. Additionally, the authors of [95] noted that steeping at 48 h had longer sprouts than 72 h steeped rice grain. However, the authors of [96][97][98][99] noted that longer steeping encourages an increase in sprout length, resulting in higher water absorption in Korean red bean, Mung bean, buckwheat, and millet, respectively.…”
Section: Effect Of Steeping and Sprouting Times On The Sprout Length ...mentioning
confidence: 78%
“…The longer steeping duration resulting in reduced sprout length was reported by [79]. The shortest sprout length was observed in Thai rice malt cultivars (Oryza sativa L. Indica) steeped for 72 h, followed by 48 and 24 h. Additionally, the authors of [95] noted that steeping at 48 h had longer sprouts than 72 h steeped rice grain. However, the authors of [96][97][98][99] noted that longer steeping encourages an increase in sprout length, resulting in higher water absorption in Korean red bean, Mung bean, buckwheat, and millet, respectively.…”
Section: Effect Of Steeping and Sprouting Times On The Sprout Length ...mentioning
confidence: 78%
“…Sorghum brews tend to be turbid and have short shelf‐life due to high residual starch content ( 32 ) . Accordingly, much emphasis is focused on malting conditions such as steeping and germination to improve the diastatic activity ( 19, 33–35 ) in sorghum malts to improve the extract yield and reduce saccharification time. Of the sorghum varieties in this study, most had a DP below the values previously reported ( 19 ) .…”
Section: Resultsmentioning
confidence: 99%
“…In barley malt, an important attribute for the activity of starch-degrading enzymes is the diastatic power, which measures the combined activity of α-and β-amylases, and for this reason it is always taken into account for the evaluation of malt. Rice malt, however, shows lower diastatic power values, and for this it seems less suitable for brewing [17]. But it contains other amylolytic enzymes that can act synergistically with α-and β-amylases [9,18,19].…”
Section: Maltingmentioning
confidence: 99%
“…Some authors performed a short steeping because increasing the steeping period directly increases the steeping losses and the mold development. The optimum steeping period for rice grains should be a balance between time, temperature and losses [17]. However in Ref.…”
Section: Maltingmentioning
confidence: 99%